A PRODUCT QUALITY, PRICE PERCEPTION, AND BRAND IMAGE ON PURCHASE DECISION - Harun, Abdul; Paludi, Salman (Management and Leadership Study Programme, 2025)
This study aims to determine the effect of product quality, price perception, and brand image on purchasing decisions of Brand Executive consumers. The approach used is a quantitative method with data collection techniques through distributing questionnaires. The sample in this study amounted to 125 respondents selected using the accidental sampling technique. Data processing was carried out with the help of SPSS version 26, and the analysis method used was multiple linear regression. The results of the study indicate that the three independent variables, namely product quality, price perception, and brand image simultaneously have a positive and significant effect on purchasing decisions. Partially, each variable also shows a significant effect, with price perception having the most dominant effect. These findings indicate that in order to improve purchasing decisions, Brand Executives need to pay attention to the price perception captured by consumers, accompanied by positive product quality and brand image.